The Twitter Revolution in the Gulf Countries - Al-Jenaibi, Badreya (Journal of Creative Communications, 2016)
The use of social media received a lot of ‘buzz’ due to the Arab Spring because of the events that unfurled in the uprisings in Tunisia and Egypt, among other places. However, although not as dramatic as overthrowing a current regime, the use of social media has been revolutionary in most areas of the Middle East, especially the most conservative societies that have been relatively closed to information that flowed without constraint. Saudi Arabia, for example, now has the largest growing Twitter community of all the nations in the Arabian Gulf. Known for its tight rein on public discourse and the flow of information, even elements of the current regime are opening doors to a new public discourse in large part due to the influence of social media. This project will explore the social media phenomenon that has had such an impact on the relatively closed societies of the Arab world, specifically on how it has changed the nature of public. The researcher used content analysis of four Gulf Cooperation Council (GCC) journalist accounts and surveyed online research publications related to the subject from two different library databases that included hundreds of peer-reviewed academic journals. Also, the researcher conducted online keyword searches for information about research publications on the subject. The article concluded that the use of Twitter is shifting the Arab people discourse and opinion in the kingdom because those opinions are being heard instead of censored. Social media is having a major impact on the conservative Saudi, Qatar and UAE societies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTczMjU4NjE2NjMwMjE3